Auxiliary Liver Graft Can Be Protected From HBV Infection in HBsAg Positive Blood Circulation - Wei, Lin; Zhang, Hai-Ming; Wan, Chi-Dan; Qu, Wei; Zeng, Zhi-Gui; Liu, Ying; Xiong, Jun; Sun, Li-Ying; Zhu, Zhi-Jun (Frontiers in Medicine, 2021)
Auxiliary grafts have a high risk of Hepatitis B virus (HBV) infection in patients with chronic HBV-related diseases. HBV-related auxiliary partial orthotopic liver transplantation (APOLT) cases were reviewed to show the results of current methods to block native-to-graft HBV transmission. Three patients received APOLT for HBV-related liver cirrhosis and a recurrent upper gastrointestinal hemorrhage between April 2015 and January 2017 by the liver transplant team of Beijing Friendship Hospital affiliated with Capital Medical University. All 3 patients were positive for HBV surface antigen (HBsAg) and had a negative HBV DNA test result before transplantation. After auxiliary transplantations, HBsAg was found to be positive in 2 patients and negative in 1 patient. To avoid graft infection of HBV, entecavir-based therapy was employed and the remnant native livers of the recipients were removed 51-878 days after liver transplantation. Then, serum conversions of HBsAg were found in all 3 cases. For the first time, this case series shows the possibility of blocking the transmission of HBV from a native liver to a graft in auxiliary transplantation by entecavir-based therapy. Among the cases, a left lobe graft was successfully implanted as a replacement of the right lobe of the recipient, which is also discussed.